Return on Assets, Return on Equity, Net Profit Margin, and Book Value Per Share on The Value of Infrastructure Sector Companies Listed on The Indonesian Stock Exchange - Anggraina, Maya; Ryanto, Fuad Ramdhan (International Journal of Economics Development Research (IJEDR), 2024)
This study aims to identify the effect of Return on Asset (ROA), Return on Equity (ROE), Net Profit Margin (NPM), and Book Value Per Share (BVPS) on firm value in the infrastructure sector listed on the Indonesia Stock Exchange (IDX). The research method used is associative research with data collection techniques through documentation studies using secondary data from the company's published financial statements and other sources. The analysis results show that simultaneously, ROA, ROE, NPM, and BVPS variables have a significant effect on firm value with a contribution of 57.2%. Although partially, these variables do not have a significant effect individually on firm value. This finding supports the signaling hypothesis theory which states that investors consider dividend changes as a signal of good earnings in the future. This study provides a deeper understanding of the factors that influence firm value in the infrastructure sector on the IDX. However, it should be noted that this study has limitations in the use of certain data and analytical methods, so the results should be interpreted in the specific context of this study and can be extended with further research that considers additional factors that may affect the value of these companies.Top of FormBottom of Form.